KEMAMPUAN MENYIMAK PESAN FIRMAN TUHAN DENGAN MENGGUNAKAN MEDIA AUDIOVISUAL BERDASARKAN PRINSIP COGNITIVE THEORY OF MULTIMEDIA LEARNING (CTML) DI JEMAAT GKN SHALOM SENTANI - Rumeni Br. Silitonga (KOHESI : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Abstract This research to describe the congregation’s ability to comprehend the message of God’s Word through the use of audiovisual media. Data were collected through direct interviews with members of the congregation following the worship service, after they had listened to the sermon presented using audiovisual media. The research employed a qualitative descriptive method to analyze the congregation’s listening ability at GKN Shalom Sentani in relation to the audiovisual presentation of scriptural messages. Findings revealed that 85% of the participants indicated that audiovisual media provided strong dual-channel stimuli (visual and auditory), which significantly enhanced their comprehension and memory of the message. This outcome aligns with the stimulus–response theory and supports the application of audiovisual media based on the principles of the Cognitive Theory of Multimedia Learning (CTML). The study recommends that church leaders and educators consider utilizing audiovisual media in the delivery of sermons, as it has the potential to serve as an effective cognitive stimulus and reinforce congregational retention of Bible messages. Keywords: Audiovisual media, Listening comprehension, Cognitive Theory of Multimedia Learning